Global burden and projections of cervical cancer attributable to unsafe sex and smoking, 1990–2034 - Jie Hu; Yajie Wang; Yan Liu; Zhengrong Cai (PLoS ONE, 2026)
Objectives To analyze global trends and attributable risks (smoking and unsafe sex) in disease burden of cervical cancer from 1990 to 2034, considering different sociodemographic index (SDI) levels. Methods Data from the Global Burden of Disease 2019 study was utilized. Quantile regression, restricted cubic spline, and Nordpred models were applied to analyze the relationship between cervical cancer age-standardized mortality rates (ASMRs), age-standardized Disability-Adjusted Life Years rates (ASDRs) and SDI, and predicted future trends. Results From 1990 to 2019, global cervical cancer ASMR declined but the total deaths increased. Unsafe sex accounted for the highest disease burden, particularly in low-SDI regions, followed by smoking. By 2034, ASMR attributed to unsafe sex and smoking is projected to further decrease globally, but an upward trend is expected in specific regions including India (unsafe sex), China (smoking) and Russian Federation (unsafe sex and smoking). Conclusion Unsafe sex is the leading risk factor for cervical cancer. Targeted strategies are needed for distinct age groups: enhanced prevention and screening for those aged 55–59 years, and optimized care for adults aged over 95 years. The key interventions, including HPV vaccination, screening, and smoking cessation programs, remain critical in low and low-middle SDI areas.